Effect of current density on accelerated corrosion of reinforcing steel bars in concrete. Issue 11 (2nd November 2018) - Nguyen, Chinh Van; Lambert, Paul
Abstract: Impressed anodic current techniques are used widely to accelerate corrosion of steel embedded in concrete in the laboratory. This paper investigates the relationship between applied current density, degree of corrosion, type of corrosion and ultimate strength of corroded beams. Twenty beams were divided into four groups with a 0.5, 1, 2.5 or 5% degree of corrosion. Current densities of 0.25, 0.5, 1.0 or 2.5 mA/cm 2 were applied to each group, respectively. The beams were flexurally tested and the reinforcing steel bars were retrieved, cleaned, weighed and the surface examined. The results demonstrated that higher current densities and degree of corrosion caused more localised corrosion. The applied current density has little effect on the degree of corrosion and on ultimate strength of the same degree of corroded beam. Based on this work, a current density of 1 mA/cm 2 is recommended for the artificial acceleration of corrosion for steel embedded in concrete.